The Effect of Family Nursing Conversations as an Add-on to Multidisciplinary Treatment in Patients with Chronic Non-Cancer Pain: A Quasi-Experimental Trial - Pernille Friis Rønne RN, MSA, PhD; Bente Appel Esbensen RN, MSciN, PhD; Anne Brødsgaard RN, MPH, PhD; Lasse Østergaard Andersen MD, PhD; Bo-Biering Sørensen MD, MPG; Carrinna Aviaja Hansen RN, MPH, PhD (SAGE Publishing, 2024)
Introduction Chronic non-cancer pain (CNCP) is a lifelong condition with radical consequences, calling for management involving patients' families. Interventions based on the family systems nursing framework by Wright and Leahey have proved beneficial in other populations but require investigation in a CNCP population. This trial assumed that family nursing conversations (FNCs) based on the family systems nursing framework would increase patients' and family members' self-efficacy concerning CNCP management. Objective To investigate whether an intervention with FNCs as an add-on to the usual multidisciplinary treatment of CNCP would have an effect on patients' and family members' self-efficacy. Additionally, to investigate any impact on family function, health-related quality of life, anxiety, and depression. Methods The trial applied a prospective non-blinded quasi-experimental design with two comparable groups of patients and family members: a historical control group (HCG) and an intervention group (IG). The intervention was executed by nurses employed at a multidisciplinary pain center in the Capital Region of Denmark. HCG data were collected before the nurses' intervention training. The primary outcome was self-efficacy. Secondary outcomes were family function, health-related quality of life, anxiety, and depression. Results In total, 58 patients and 85 family members were included. The primary outcome, self-efficacy, detected no statistically significant between-group differences in mean change for patients, p  = .990, or family members, p  = .765. A statistically significant effect in favor of the IG was found in between-group differences in mean change in patients' behavioral family function, p  = .034, and anxiety, p  = .031. No statistically significant between-group differences were detected in family members' secondary outcomes. Conclusion The intervention had no effect on patients' or family members' self-efficacy but a positive effect on patients' behavioral family function and anxiety. The intervention was deeply affected by the COVID-19 pandemic. Hence, any results should be interpreted with caution.